Utilization Of Mobile Phones To Apply Blended Learning At Higher Education: Computer Subject at State Vocational High School 1 BENGKULU - ., Paidi; Wibawa, Basuki (International Journal of Engineering and Technology, 2018)
The application of blended learning at vocational high schools is one of the solutions to increase interest in learning to students. The preparation of software is easily accessible on gadgets, thus the delivery of material can be done online. Tasks and practices may be applied in class according to teacher's instruction. By data in the form of the amount of gadgets used by students reaching 100 percent, the delivery of material by video, voice recordings to learning materials can be received easily. The task and practice plan project is delivered at the beginning of lesson with targets determined in accordance with the applicable curriculum. By applying the blended learning method by utilizing gadgets, it can be one alternative for developing and increasing interest in learning to students.Â Â